MANAJEMEN RISIKO PADA LABORATORIUM BIOFARMASETIKA DAN ANALISIS FARMASI FAKULTAS FARMASI UNIVERSITAS AIRLANGGA - Indra Oditya Putra (The Indonesian Journal of Occupational Safety and Health, 2018)
The laboratory is a place of activities for research, education and product quality test. The laboratory is also a place to conduct experiments and research that has a source of danger and can cause work accidents. The research objectives are aware of risks and hazards in the laboratory, hence the need to identify hazards, risk assessments, and risk control. Data collection method used is observasional, based on the analysis of properties and data analysis hence this research including descriptive research. In review from the time of the study including cross sectional. The sample of this research is 6 laboratory personnel in 2 laboratories. The data used are the primary data from the observation, interview and questionnaire and secondary data obtained from the Faculty of Pharmacy. The results of the study can identify as many as 8 hazards. In the risk assessment obtained the highest danger level is high risk. High risk risk level of 3 hazards ie HCl solution spills, nitric acid spills, sulfuric acid spills. This laboratory is still quite dangerous because it is still found high risk. The existing risk control in the laboratory is well implemented and needs to be improved by the use of Personal Protective Equipment (PPE). Keywords: hazard identification, risk assessment, risk control